رقمنة قطاع التربية و اثرها على الاتصال الوظيفي بالجزائر - مسعودة سماح محبوبي; وفاء حمدون; د/ رقيو لقلوق (جامعة عمار ثليجي بالاغواط, 2025)
الملخص تبحث هذه الدراسة في أثر الرقمنة على الاتصال الوظيفي في قطاع التربية بالجزائر، باعتماد مديرية التربية لولاية البيض كنموذج تطبيقي. وقد جاء هذا في ظل التحول الرقمي الذي يشهده القطاع، من خلال إدماج أدوات مثل البريد المهني، المنصات الرقمية، ونظم المعلومات الإدارية. سعت الدراسة إلى تحديد مدى مساهمة هذه الرقمنة في تحسين الاتصال الداخلي بين الإدارات والموظفين، وكشفت عن تحسن نسبي في الأداء الوظيفي، رغم وجود تحديات مثل ضعف التكوين، نقص الوسائل، وغياب ثقافة رقمية فعالة. اعتمدت الدراسة على المنهج الوصفي التحليلي، وأُجريت مقابلة مع مدير التربية لجمع بيانات ميدانية. كما تم توظيف مقاربات نظرية (تكنولوجية، سيبرانية، سوسيولوجية وظيفية) لتفسير النتائج. خلصت النتائج إلى أن الرقمنة ساهمت في تطوير الاتصال الوظيفي، لكنها تتطلب دعمًا هيكليًا وبشريًا أكبر لتحقيق فعاليتها الكاملة. الكلمات المفتاحية: الرقمنة، الاتصال الوظيفي، قطاع التربية، مديرية التربية، الجزائر، الموارد البشرية، التحول الرقمي، الاتصال التنظيمي. Abstract (Condensed) This study explores the impact of digitalization on functional communication within Algeria’s education sector, taking the Directorate of Education of El Bayadh Province as a case study. In light of the sector's ongoing digital transformation—through tools such as professional emails, digital platforms, and administrative information systems—the study examines how digital tools influence internal communication and administrative coordination. Using a descriptive-analytical approach and relying on a semi-structured interview with the Director of Education, the research reveals a partial improvement in functional communication due to digital tools. However, several challenges persist, including limited staff training, lack of infrastructure, and the absence of an integrated digital culture. The study employs multiple theoretical frameworks (technological, cybernetic, and sociological-functional) to interpret the findings. The results highlight that digitalization enhances internal communication, yet its success depends on stronger structural and human resource support. Keywords: Digitalization, Functional Communication, Education Sector, Directorate of Education, Algeria, Human Resources, Digital Transformation, Organizational Communication.